Neural Cell Adhesion Molecule (NCAM) a Serum Biomarker Indicative for the Severity of Cervical Spondylotic Myelopathy. Issue 4 (May 2020) - Akshota, Nissim; Friedlander, Alon; Hershkovich, Oded; Gurevich, Michael; Givon, Uri; Sakhini, Mojahed; Achiron, Anat
Abstract : Study Design: Peripheral blood samples were obtained from 25 patients with cervical spondylotic myelopathy (CSM) and 13 healthy volunteers. Objectives: Our aim was to investigate the significance of neurodegenerative biomarkers in patients with CSM and correlate their expression with CSM severity. Summary of Background Data: CSM is a common disorder involving chronic progressive compression of the cervical spinal resulting in progressive neurological impairment that ranges from mild tingling in the upper limbs to complete quadriplegia. However, the immunological background related to the neurodegenerative damage and its significance in CSM is still unclear. Methods: Protein expression profiles of 14 neurodegenerative biomarkers were measured by multiplex Luminex bead assay and further analyzed by group comparison statistics, correlation studies, and receiver-operating characteristic analysis. Results: Eleven of 14 biomarkers were significantly elevated in CSM patients as compared with healthy subjects ( P <0.05). Specifically, the clinical severity of CSM on the scales of Nurick and modified Japanese Orthopedics Association scale (mJOA) was inversely related to neural cell adhesion molecule (NCAM) levels ( r =−0.529, P =0.007; r =−0.519, P =0.001, respectively). Conclusions: Serum level of neural cell adhesion molecule may serve as a diagnostic biomarker correlating with the severity of CSM.